2019
DOI: 10.1080/19396368.2019.1600171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidative enzymes in the seminal plasma of infertile men: Contribution to classic semen quality analysis

Abstract: Protein expression/activity of antioxidative defense enzymes (AD) in seminal plasma of fertile men might be used as biomarkers of male fertility status. To test this concept, the present study examined the semen parameters of males among 14 normal idiopathic (normozoospermia) and 84 subnormal (teratozoospermia, oligoteratozoospermia, oligoasthenoteratozoospermia) infertile individuals\. We investigated levels of protein expression/activity of Cu, Zn superoxide dismutase (CuZnSOD), manganese superoxide dismutas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…On the other hand, coiled tails are formed during sperm epididymal maturation, probably because of the weakness of dense fibers [37]. Other studies in men showed significant correlations between sperm morphology and the content and/or activity of some antioxidant enzymes in SP such as superoxide dismutase (SOD), catalase (CAT) and GPX [38,39]. Against this background, it is suggested that GSTM3 in SP plays a key role during epididymal maturation and is proposed as a sperm morphology biomarker candidate.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, coiled tails are formed during sperm epididymal maturation, probably because of the weakness of dense fibers [37]. Other studies in men showed significant correlations between sperm morphology and the content and/or activity of some antioxidant enzymes in SP such as superoxide dismutase (SOD), catalase (CAT) and GPX [38,39]. Against this background, it is suggested that GSTM3 in SP plays a key role during epididymal maturation and is proposed as a sperm morphology biomarker candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Las anormalidades se clasifican en tres grupos: primarias (aquellas que afectan la cabeza y el acrosoma del espermatozoide), secundarias (las que afectan la pieza o tracto intermedio) y terciarias (las que causan daño de la cola). Otra escala de clasificación, que va acorde al órgano donde puede haberse generado la anormalidad, las clasifica en anomalías primarias y secundarias (Otasevic et al, 2019).…”
Section: Características Seminalesunclassified
“…Molecules showing association with (in)fertility are innumerable, but association between variables is not definitory of function in a general population. Markers for sperm dysfunction [ 218 ] and (in)fertility have been detected in spermatozoa [ 27 , 190 , 219 , 220 ] and in the SP [ 221 , 222 ] of many species, including humans [ 218 , 222 , 223 , 224 , 225 ] and livestock [ 70 , 226 ]. They vary from gene presence [ 227 ], markers of Sertoli cell function [ 228 ], proteins [ 36 , 229 , 230 , 231 ], anti-oxidative enzymes [ 223 , 232 , 233 ] and metabolites [ 234 , 235 , 236 ] to exosome-associated molecules [ 237 , 238 ] and microRNAs [ 181 , 239 , 240 , 241 ].…”
Section: What Else Can Be Done With Our Current Knowledge Of Sp?mentioning
confidence: 99%